Distance teaching for the third world : the lion and the clockwork mouse, incorporating a directory of distance teaching projects - Young, Michael Dunlop (Routledge library editions. Development., 2011)
This reissue, first published in 1980, is based on the experiences of the International Extension College in developing distance teaching. The volume begins by reviewing the world problems of educational quality and quantity, and then examines the ways in which print, broadcasts and group study have been used to train teachers, to improve classroom education, to teach by correspondence out of school, and to support rural development. It then considers how that experience can be used, perhaps by creating a network of radio colleges, to supplement and extend existing schools and colleges. Finall.